PNLD Campo: uma análise do Programa à luz das políticas educacionais para o campo (2011-2020) - Figueira, Nayara (2021)
The conjecture about Field Education and its subjects have been transformed over the years, and, due to the strong action of the Rural Social Movements, it has gained space in governmental agendas and in the elaboration of public policies. In this sense, this research is related to public policies on education for the peasant population, having as object of study the National Rural Textbook Program (PNLD Campo). Beyond the analysis of textbooks, the main objective is to analyze the PNLD Campo as a public policy, in the conditions from its emergence to its closure. To this end, this qualitative, bibliographical and documental research uses some scientific productions from CAPES and BDTD portals, as well as renowned theoreticians, to guide the discussions about Rural Education, such as the contributions of Arroyo (2005), Caldart (2008, 2012), Frigotto (2010) and Molina (2011). Composing the documental references, the Informes/FNDE are used for analysis. Thus, this research is organized into three chapters, starting with the political situation in Brazil between 2011 and 2020; then, we characterize rural education, discussing the confrontation between rural and rural education; finally, we discuss the public policies for rural education until we reach the analysis of the central object, which is the PNLD Campo. In the considerations, it is possible to verify the impacts of governmental actions and their reflexes on Field Education, which, despite being on governmental agendas, does not appear with the same urgency as the Movements, and even having acquired rights, they are not guaranteed, as indicated by the publication of Decree 10.252, of February 20, 2020, demonstrating that the achievements in the scope of public policy are deliberately cancelled, like many other social educational policies.